1986
DOI: 10.1891/0886-6708.1.2.85
|View full text |Cite
|
Sign up to set email alerts
|

Gender, Lifestyles, and Victimization: Beyond Routine Activity

Abstract: Using data from a national survey of high school seniors and a study of high school students in Tucson, Arizona, this paper tests hypotheses about gender, routine activities, and delinquent activities as correlates of teenage victimization. The results are consistent with the hypotheses and suggest the following generalizations: (1) activities which involve the mutual pursuit of fun are more victimogenic than activities which passively put people at risk; (2) delinquent activity is positively related to victim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

26
283
4
4

Year Published

1999
1999
2017
2017

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 341 publications
(317 citation statements)
references
References 0 publications
26
283
4
4
Order By: Relevance
“…People, who spend more time with delinquent friends and/or in places where crimes take place, are more at risk of being victimized and also have more criminal opportunities (e.g., Jensen and Brownfield 1986;Lauritsen, Sampson, and Laub 1991;Sampson and Lauritsen 1990;Schreck, Wright and Miller 2002). In addition, impulsivity and low self-control can directly increase victimization and offending (e.g., Gottfredson and Hirschi 1990;Jennings et al 2010;Piquero et al 2005;Pratt et al 2014), but also indirectly through the association between low self-control and increased time spent in criminogenic settings (e.g., Schreck 1999;Schreck, Stewart, and Fisher 2006).…”
Section: Risk Factors For Traditional Crime and Cybercrimementioning
confidence: 99%
“…People, who spend more time with delinquent friends and/or in places where crimes take place, are more at risk of being victimized and also have more criminal opportunities (e.g., Jensen and Brownfield 1986;Lauritsen, Sampson, and Laub 1991;Sampson and Lauritsen 1990;Schreck, Wright and Miller 2002). In addition, impulsivity and low self-control can directly increase victimization and offending (e.g., Gottfredson and Hirschi 1990;Jennings et al 2010;Piquero et al 2005;Pratt et al 2014), but also indirectly through the association between low self-control and increased time spent in criminogenic settings (e.g., Schreck 1999;Schreck, Stewart, and Fisher 2006).…”
Section: Risk Factors For Traditional Crime and Cybercrimementioning
confidence: 99%
“…Unstructured and unsupervised activities coupled with risky lifestyles, such as substance use, bring together willing offenders and suitable victims in criminogenic environments. In support of theoretical expectations, subsequent research has discovered that factors associated with violent offending, such as being male, minority status, young, and having a prior offending history, are also associated with violent victimization (Daday, Broidy, Crandall & Sklar 2005;Jensen and Brownfield 1986;Lauritsen, Sampson, & Laub 1991;Sampson and Lauritsen 1990). …”
Section: Introductionmentioning
confidence: 95%
“…Prior research has suggested that offenders and victims are often one and the same [4,6,9,28,29], and this finding is not unique to the United States (e.g., [21,[30][31][32]. Furthermore, more recent studies have elaborated on the shared commonality of risk factors for offending and victimization with a particular focus on routine activities/lifestyles and social context [3,19].…”
Section: Discussionmentioning
confidence: 99%
“…Studied at length and created by Cohen and Felson (1979) and Hindelang, Gottfredson, and Garofalo (1978), this perspective views victimization as a by-product of ordinary activities such as alcohol consumption that bring easily targeted individuals into contact with potential offenders [1][2][3]. Drawing further on the work of the earlier theorists, Jensen and Brownfield (1986) went a step further by viewing a person's criminal activity as a lifestyle that also carries with it a high risk of victimization [4]. This perspective emphasizes that criminal activities are often done in group settings whereby individuals situate themselves in a social context of greater exposure to potential offenders [5].…”
Section: Introductionmentioning
confidence: 99%